2000
DOI: 10.1002/0470868678.ch15
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Effects of Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is characterised by an inappropriate/excessive inflammatory response of the lungs to respiratory pollutants, mainly tobacco smoking.Recently, besides the typical pulmonary pathology of COPD (i.e. chronic bronchitis and emphysema), several effects occurring outside the lungs have been described, the socalled systemic effects of COPD. These effects are clinically relevant because they modify and can help in the classification and management of the disease.The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
283
0
50

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(341 citation statements)
references
References 52 publications
(68 reference statements)
8
283
0
50
Order By: Relevance
“…Hypoxemia could well be relevant for nutritional status, as tissue hypoxemia per se can cause cellular energetic alterations, leading to an increased metabolic rate and reduced protein synthesis (Agusti et al, 2003). Moreover, in COPD, systemic inflammation is thought to show a causal relationship to nutritional depletion and is particularly prevalent in underweight patients (Gan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxemia could well be relevant for nutritional status, as tissue hypoxemia per se can cause cellular energetic alterations, leading to an increased metabolic rate and reduced protein synthesis (Agusti et al, 2003). Moreover, in COPD, systemic inflammation is thought to show a causal relationship to nutritional depletion and is particularly prevalent in underweight patients (Gan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous comprehensive study of patients with chronic respiratory failure (CRF), the relationship between malnutrition and functional indices has been analysed while summarizing over different aetiologies, so that diseasespecific characteristics of the underlying mechanisms may have been obscured (Cano et al, 2002). Indeed, the majority of data on pulmonary cachexia refers to COPD and suggests a multifactorial nature of malnutrition (Congleton, 1999;Agusti et al, 2003). In COPD, lung hyperinflation seems to be one factor of interest as it results in a mechanical disadvantage, although the contribution of increased work of breathing to cachexia is not clear (Engelen et al, 1999;Mannix et al, 1999;Budweiser et al, 2005Budweiser et al, , 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with COPD, particularly when the disease is severe and during exacerbations, have evidence of systemic inflammation, measured either as increased circulating cytokines, chemokines and acute phase proteins, or as abnormalities in circulating cells [5][6][7]. Smoking itself may cause systemic inflammation, for example, and increased total leukocyte count, but in COPD patients the degree of systemic inflammation is greater.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…(18,19), lung growth (20), gender (21,22), socioeconomic status (23) and nutrition (24). Furthermore, recently, it has been reported that systemic inflammation could be involved in the pathogenesis of COPD (5)(6)(7), and that COPD patients are at increased risk for several comorbidities including myocardial infarction, osteoporosis, depression and diabetes (1). However, it is still unclear whether such diseases affect the prevalence of COPD.…”
Section: F I G U R E 3 T H E P R E V a L E N C E O F Cop D A C C O mentioning
confidence: 99%
“…Recently, the high worldwide prevalence of COPD has been reported to be more than 9% in Europe (2), more than 11% in Latin America (3), and 8.6% in Japan (4). In addition, new aspects of COPD, such as systemic consequences and comorbidities, have received attention (5)(6)(7). It has been reported that up to 25% of the population older than 65 years suffers from two comorbid conditions and up to 17% have three (8).…”
Section: Introductionmentioning
confidence: 99%